2012
DOI: 10.1152/ajpendo.00163.2012
|View full text |Cite|
|
Sign up to set email alerts
|

Transformation of postingestive glucose responses after deletion of sweet taste receptor subunits or gastric bypass surgery

Abstract: -The glucose-dependent secretion of the insulinotropic hormone glucagon-like peptide-1 (GLP-1) is a critical step in the regulation of glucose homeostasis. Two molecular mechanisms have separately been suggested as the primary mediator of intestinal glucose-stimulated GLP-1 secretion (GSGS): one is a metabotropic mechanism requiring the sweet taste receptor type 2 (T1R2) ϩ type 3 (T1R3) while the second is a metabolic mechanism requiring ATP-sensitive K ϩ (KATP) channels. By quantifying sugar-stimulated hormon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(100 citation statements)
references
References 85 publications
6
93
1
Order By: Relevance
“…Second, it promotes metabolism and generates ATP using substrates supplied by glycolysis of glucose entered into β-cells. Insulin secretion was studied in β-cells obtained from mice lacking the T1R3 gene [18]. Although the gross insulin secretory response to glucose is not changed, analysis of exocytotic fusion of the insulin granules revealed that rapid exocytosis is markedly attenuated in T1R3-null β-cells.…”
Section: Discussionmentioning
confidence: 99%
“…Second, it promotes metabolism and generates ATP using substrates supplied by glycolysis of glucose entered into β-cells. Insulin secretion was studied in β-cells obtained from mice lacking the T1R3 gene [18]. Although the gross insulin secretory response to glucose is not changed, analysis of exocytotic fusion of the insulin granules revealed that rapid exocytosis is markedly attenuated in T1R3-null β-cells.…”
Section: Discussionmentioning
confidence: 99%
“…Some groups have hypothesized that T1R2/T1R3 does not function as an obligate heterodimer (42,43), but rather each component functions independently as a homodimer, consistent with the N-terminal domains of both T1R2 and T1R3 containing ligand-binding sites and changing conformation in response to artificial sweeteners (13). The homodimerization model has found support from Shibata and co-workers (55), who have investigated sweet taste receptor activity in cultured 3T3-L1 and adipose tissue stromal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Literature suggests that T1R2 and T1R3 are capable of individually responding to tastants rather than functioning as an obligate heterodimer (25,42,43). To directly address the possibility of T1R2 and T1R3 homodimer activity in preadipocytes, we produced T1R2/T1R3 DKO eMSCs.…”
Section: Sweet Taste Receptors T1r2 and T1r3 Are Expressed Throughoutmentioning
confidence: 99%
“…Mouse pancreatic islets were isolated by using collagenase (Gotoh et al 1985). Isolated islets were preincubated for 1 h in KRH buffer.…”
Section: Measurement Of Insulin Secretionmentioning
confidence: 99%
“…Subunits of the sweet taste receptor are also expressed in extragustatory organs including enteroendocrine cells (Bezencon et al 2007, Margolskee et al 2007, Jang et al 2010, pancreatic b-cells (Nakagawa et al 2009, Geraedts et al 2012, Kyriazis et al 2012 and adipocytes (Masubuchi et al 2013). Unlike taste cells of the tongue, the expression level of T1R2 is much lower compared to that of T1R3 in these cells (Masubuchi et al 2013, and a homodimer of T1R3 may function as the sweet taste-sensing receptor (Masubuchi et al 2013.…”
Section: Introductionmentioning
confidence: 99%